2015
DOI: 10.1136/bmjopen-2015-007700
|View full text |Cite
|
Sign up to set email alerts
|

REpeated AutoLogous Infusions of STem cells In Cirrhosis (REALISTIC): a multicentre, phase II, open-label, randomised controlled trial of repeated autologous infusions of granulocyte colony-stimulating factor (GCSF) mobilised CD133+ bone marrow stem cells in patients with cirrhosis. A study protocol for a randomised controlled trial

Abstract: IntroductionLiver disease mortality and morbidity are rapidly rising and liver transplantation is limited by organ availability. Small scale human studies have shown that stem cell therapy is safe and feasible and has suggested clinical benefit. No published studies have yet examined the effect of stem cell therapy in a randomised controlled trial and evaluated the effect of repeated therapy.Methods and analysisPatients with liver cirrhosis will be randomised to one of three trial groups: group 1: Control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…However, as discussed earlier, our group had an expectedly worse 12‐month survival and needed special attention. Moreover, other studies have also excluded the similar group of patients and some have already reported improved outcomes with G‐CSF in patients with ACLF …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed earlier, our group had an expectedly worse 12‐month survival and needed special attention. Moreover, other studies have also excluded the similar group of patients and some have already reported improved outcomes with G‐CSF in patients with ACLF …”
Section: Discussionmentioning
confidence: 99%
“…Three independent physicians assessed the suitability of the patients for the trial. Etiology of cirrhosis was based on the history of significant alcohol intake, positive viral markers or autoimmune markers, and features of metabolic syndrome …”
Section: Methodsmentioning
confidence: 99%
“…More recently, the Repeated AutoLogous Infusion of Stem cells In Cirrhosis (REALISTIC), a multicenter, phase II, open-label, randomized controlled trial of repeated autologous infusion of G-CSF-mobilized CD133? bone marrow stem cells in patients with cirrhosis, was announced in the UK [55]. Although the effectiveness and potential applications of cell therapy have been reported, several problems need to be overcome.…”
Section: Autologous Bone Marrow Cell Injection Therapy and Related Trmentioning
confidence: 99%
“…Importantly, the heterogeneity and the role of macrophages in human liver fibrosis are less well understood than in mouse models [24] . Nevertheless, there is preliminary clinical evidence that infusion of BM-derived cells might be beneficial in end-stage liver disease, and a large controlled multicenter clinical trial, that is, the Repeated Autologous Infusions of Stem cells in Cirrhosis (REALISTIC), in which the outcome on cirrhosis in patients will be assessed that either receive G-CSF alone or G-CSF followed by repeated infusions of hematopoietic stem cells compared with standard conservative management [25] . However, although the results of this trial need to be awaited, recovery from advanced cirrhosis to normal tissue might be somewhat limited by the occurrence of irreversible matrix crosslinking conferring a relative resistance to degradation [26] .…”
Section: Mechanisms Of Liver Fibrosis Regressionmentioning
confidence: 99%